Pengembangan E-Modul Berbasis Canva Model ADDIE Mata Pelatihan Pembuatan Konten Video Interaktif dalam Pembelajaran pada Pelatihan TIK MTS di Balai Diklat Keagamaan Surabaya - Rejeki, Sri; Leksono, Ibut Priono; Rohman, Ujang (LP. Ma'arif Janggan Magetan, 2023)
In the initial study, information was obtained that there was no development of teaching materials in accordance with the demands of technological developments. Besides that, in fact the use of e-module teaching materials in training is still minimal. For this reason, it is necessary to develop this e-module to assist the learning process. The purpose of this study is to determine the feasibility, practicality and effectiveness of the developed e-module. The type of research used is development research. The development of e-modules in this study uses the ADDIE model. The ADDIE development model consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. At the analysis stage, a needs analysis is carried out, such as an analysis of the curriculum, teaching materials, and materials. In the design phase, an interactive e-module development design plan was created. The development stage in this research is e-module development, review, expert validation test, namely media experts, design experts, and material experts. The implementation stage in this study is the implementation of e-module trials in learning activities. E-module trials were carried out in small groups and large groups. At the evaluation stage, a questionnaire was given to the responses of the training participants. The validation results of the MTs ICT Training e-module by design experts, media experts and material experts obtained successive percentages of 90%, 88% and 86.5% which were declared very valid. The MTs ICT Training E-module received very good responses from the training participants in small and large group trials with successive percentages of 86.5% and 85.83%, this shows that the E-module is effective for use. From the results of the paired t-test using SPSS statistical software, a p-value of 0.00 was obtained which indicated that there was a significant average difference between the pre-test and post-test values in the large group trial.